Upaya Meningkatkan Aktivitas dan Hasil Belajar Snowball Throwing di Kelas IX-3 SMP Negri 4 Cileungsi Kabupaten Bogor - Purnama Sari (JURNAL KAJIAN ISLAM MODERN, 2020)
This Classroom Action Research was motivated by the land problems found when carrying out learning, namely the low learning activity of students in participating in the Social Sciences (IPS) learning process and the low social studies learning outcomes of class IX-3 students at SMP Negeri 4 Cileungsi, Bogar Regency. This research is an action research that is carried out systematically on various actions. The research steps consist of several stages, namely planning, implementation, observation, and reflection. The research subjects were students of class IX-3. Determining the problem as a solution the researcher uses the Snowball Throwing learning model to improve activities and learning outcomes. The results showed (1) there was an increase in student learning activities from 74.75% of the first cycle to82.75% in the second cycle, this indicates an increase of 8% thus the Snowball Throwing Learning Model can improve student learning activities (2) there is an increase in student learning outcomes from 72.22% in the first cycle to 86.11% in the second cycle this shows an increase of 13.89%, thus Snowball Throwing Learning can improve student learning outcomes. From the results of the research data, it can be concluded that the Snowball Throwing learning model can improve learning activities and student learning outcomes